United Kingdom : Financial Sector Assessment Program-Select Issues in Systemic Risk Oversight and Macroprudential Policy. (IMF Staff Country Reports; Country Report, 2022)
The United Kingdom's macroprudential policy framework has proven its effectiveness. After the Global Financial Crisis (GFC) of 2007-09, the United Kingdom assigned the Bank of England (BOE) a clear financial stability mandate, created a new Financial Policy Committee (FPC) to set macroprudential policy, and shifted to a "twin peaks" model of financial oversight. The 2016 Financial Sector Assessment Program (FSAP) concluded that the new framework appeared appropriate for effectively conducting macroprudential policy. However, the framework was then relatively new. The 2021 FSAP represents an opportunity to review its performance in building systemic resilience through the financial cycle, including the market volatility resulting from the Brexit vote and the COVID-19 pandemic.